Dirty work och professionalisering - Linnéa Holmberg (Educare)
The concept of teaching, previously primarily reserved for formal school activities, has today a prominent position in the educational assignment for preschool and school-age educare. The study examines how this concept is managed by preschool- and school-age educare teachers and highlights how talking about teaching seems both troublesome and useful. Analytical interest is directed at how discursive boarder work is staged in order to preserve existing professional territories but also to gain new legitimacy. The use of the concept of teaching risks undermining the specificity of the professional roles and is described as an undesirable task – dirty work. At the same time, the concept serves as a usable resource to enhance the credibility of preschool and school-age educare teachers. Talking of teaching seems appropriate to use outwards, to show that the changes in the professional assignment are complied with. However, it seems inappropriate to apply the concept of teaching in the actual work with children. Therefore, the concept –imposed by educational policy authorities – does not change the work of preschool and school-age educare teachers but, nevertheless. contributes to its professionalization.